Personal trainers are confident in their ability to provide nutrition care: a cross-sectional investigation. (November 2016) - Barnes, K.; Desbrow, B.; Ball, L.
Abstract: Objective: To measure the self-perceived competence of Australian personal trainers in providing nutrition care. Study design: Cross-sectional online survey. Methods: A validated survey was used to measure confidence in the ability to provide nutrition care among a snowball sample of 142 Australian-based personal trainers. The survey used 5-point Likert scale statements across four nutrition related constructs: knowledge; skills; communication and counselling; and attitudes. Scores for each construct were averaged and summed to provide a self-reported nutrition competence score as a percentage. Pearson Chi-squared analyses were used to identify associations between demographic variables and competence scores, and associations between construct scores. Results: Personal trainers felt confident to provide nutrition care for all clients (mean score 76%; 'very confident'). Greater confidence in nutrition knowledge was seen in personal trainers with greater experience (χ 2 = 6.946, P = 0.008) and education higher than a certificate IV (χ 2 = 5.079, P = 0.024). Greater confidence in nutrition knowledge was also associated with greater confidence in nutrition skills (χ 2 = 49.67, P ≤ 0.001) and more favourable attitudes towards providing nutrition care (χ 2 = 4.73, P = 0.03). Conclusions: Personal trainers feel confident in their ability and show favourable attitudes towards providing nutrition care to clients. This workforce has the potential to support lifestyle modification for chronic disease prevention. Highlights: Personal trainers are confident in their ability to provide nutrition care. Personal trainers report providing nutrition care is a good use of their professional time. Confidence was lowest in nutrition knowledge, and highest in communication and counselling. As a workforce, personal trainers may be useful to facilitate changes in dietary behaviours. Education on how to provide nutrition care within limitations of professional scope is needed.